2021
DOI: 10.1007/s00784-021-03797-9
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behaviour of dental crowns made from a novel high-performance polymer PEKK

Abstract: Objectives The aim of this study was, firstly, to analyse the long-time fatigue behaviour of crowns constructed from a novel polyetherketoneketone (PEKK) polymer, using artificial prepared teeth. Secondly, to determine the effect of the material’s stiffness that used as an artificial prepared tooth on the fatigue life of the PEKK crowns in comparison to human prepared teeth. Methods Veneered crowns with a PEKK framework were constructed on three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Regarding PEKK, in vitro studies and short-term clinical reports have evaluated its use in dentistry for implant-supported dental prostheses with favorable outcomes [40,41]. However, little is known yet about the mechanical response of PEKK as a framework material for implant-supported full-arch prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PEKK, in vitro studies and short-term clinical reports have evaluated its use in dentistry for implant-supported dental prostheses with favorable outcomes [40,41]. However, little is known yet about the mechanical response of PEKK as a framework material for implant-supported full-arch prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies and short-term clinical reports have evaluated the use of PEKK in dentistry for implant supported dental prostheses with favourable outcomes [41,42]. A recent in vitro study concluded that, although PEEK and PEKK implant abutments with titanium bases demonstrated adequate fracture resistance, before recommending PEKK or PEEK as alternative implant abutments materials, further studies are needed in order to evaluate their long-term performance [15].…”
Section: Discussionmentioning
confidence: 99%
“…The other 6 samples of each group (MF, PF) were subjected to dynamic mechanical loading using a commercial pneumatic setup (“Dyna-Mess TP 5kN HF”, DYNA-MESS Prüfsysteme GmbH, Stolberg, Germany). 1.2 million cycles were applied with a load between 20 and 200 N at 2 Hz in distilled water 37 ± 2 °C to simulate approximately 5 clinical years [ 18 , 24 , 25 ]. Specimens were fixed in a specimen holder positioned so that the forces could act directly on the center and perpendicular to the occlusal surface using a metal stylus with a 5-mm-diameter spherical tip in a small basin connected by a temperature-controlled reservoir of purified water as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%